Creación de un manual de identidad gráfica para renovar la imagen corporativa de la empresa Telemática, Lima, 2019 - Urbina Carrión, César David (2019)
This research seeks to renew the corporate image of Telematica company by creating a graphic identity manual. Since the graphic part has become a key point for the identity and image of the company. In the case of Telematica, although it has been in the market for years promoting the benefits of the geographic information system, closely related to technology, it lacks of a graphic line that communicates a modern and current concept. For this, it was taken into account to make a diagnosis with the company's staff and Telematica directors to find out the perception they have about the company and then it will be possible to give way to the creation of the graphic identity manual according to the data collected. The study was conducted through a mixedclass Research-Action design. For data collection a survey and an interview were used. Likewise, the level of research that was applied was descriptive because I detail everything corresponding to the new guidelines that were granted to the imagotype, in order to reach the innovation of the corporate image of Telematica company. Finally, an expert judgment was conducted to evaluate and determine whether the proposal of the graphic identity manual actually generates value for Telematica company.